CONSTITUENT POWER IN VENEZUELA AS AN EMPOWERMENT OF PEOPLE'S POWER - Gonzalez Broquen, Ximena (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2017)
In Venezuela, a good will to change, and in particular to transform the inherited bourgeois state of the IV Republic, has sealed the proyect of Hugo Chavez since his first political act as president, when he established a milestone in its campaign conducting the constituent process in 1999. This process aimed to re-articulate the relation between the constituent power and constituted power. The fundamental regulatory changes from that date in Venezuela, which have led to a re-articulation of constituent power as a permanent constituent people's power, are analyzed in this text.